The freaks came out to write : the definitive history of the Village Voice, the radical paper that changed American culture - Romano, Tricia (PublicAffairs, 2024)
"You either were there or you wanted to be. The Freaks Came Out to Write is the definitive oral history of The Village Voice-a New York City institution. Roaming its cramped, chaotic halls were the people who had written the first stories about the Stonewall Riots and the gay rights movement; who had advocated for civil rights before it was mainstream. The Voice was the first to cover hip-hop, the avant-garde art scene, and the AIDS crisis with urgency and seriousness when other papers were dismissing it as "the gay disease." It invented new forms of criticism and storytelling, revolutionized journalism, and covered cultural and political moments, often long before big outlets like the New York Times did. The book features interviews with iconic voices from the paper's early years, such as Norman Mailer, who co-founded the paper in 1955, and Mary Perot Nichols, who battled weekly with the infamous Robert Moses, and whose writing in the Voice saved countless New York City landmarks from destruction. Wild tales are told by Robert Christgau, the self-appointed "Dean of American Rock Criticism," and Wayne Barrett, who in the 80's was the first reporter to uncover Donald Trump as a huckster and corrupt con artist. In The Freaks Come Out to Write, Tricia Romano, who worked at the Voice during the 90's and 2000's, pays homage to the Voice. She will tell the story of American journalism, American culture, and how the Internet (and Rupert Murdoch) killed the most famous alt-weekly of all time"--